HEALTHY ALCOHOL POLICY AS AN INJURY PREVENTION STRATEGY. (7th October 2012) - Connor, J
Abstract : Alcohol's contribution to injury at both individual and population level is indisputable, and it is commonly identified as the most important single risk factor. Reduction in hazardous patterns of drinking is required for prevention of injury as well other harms, and is achievable through a synergistic mix of evidence-based alcohol policies. There is already substantial scientific consensus about effective policies, which are largely environmental rather than individual-focused and include the effective control of commercial alcohol interests. Injury prevention has much to gain from modifying such a potent up-stream determinant. Healthy alcohol policy is not just needed for the rich world but for low and middle-income countries where promotion of alcohol is aggressive and largely unregulated. Injury prevention experts have a important role to play in advocating effective control of the supply and promotion of alcohol, as it is a major primary prevention strategy for injury in all parts if the world. Paul Quigley: There has been growing recognition in New Zealand of the amount of social and financial harms that excessive alcohol consumption causes. This is across the wide spectrum of alcohol abuse, from recreational binge drinking through to the chronic health consequences of alcohol addiction. There is currently a unique opportunity to make societal change around the way we consume alcohol as part of evolving legislative change. As part of that change it became evident that there is very poor data about the actual burden of alcohol harms when related to health presentations and in particular injury. I will be presenting how there is a vital role acute services can offer, Emergency Departments, Ambulance and Police in regards to providing an accurate picture of alcohol harm. I will discuss how through relatively simple means accurate data can be obtained be health professionals that can help guide law and enforcement agencies make change that can have real impact on these harms. I will include examples of collaborative work with the Wellington City Council and other agencies working towards a safer city.